Implementasi Pendidikan Agama Islam Di SDN 4 Selat Tengah Kecamatan Selat Kabupaten Kapuas - Hairunnisa, M.Pd. (STAI Kuala Kapuas, 2023)
This study aims to obtain an overview of the extent to which the implementation or implementation of Islamic Religious Education at The State Elementary School 4 Central Strait and find out what factors affect the success of Islamic Religious Education will take place properly and successfully according to the circumstances with the goals expected by educators. The technique of taking data uses qualitative methods, the tools used in this study are in the form of si observation, interviews, and commentation. The basic assumption is stated that the implementation in a learning will run well and be successfully supported by the ability of teachers in achieving curriculum targets, the use of appropriate methods and tools in learning, the effectiveness of appropriate time and facilities and the preparation of tools that are always available at each time of learning. Based on the above assumptions, the author developed a hypothesis that the implementation of Islamic Religious Education in SDN 4 Central Strait was not carried out properly due to several factions. The subjects and objects in this study were Islamic Teachers and all 150 students of SDN 4 Selat Tengah who were Muslims. Based on the results of the study, the implementation of Islamic Religious Education at SDN 4 Selat Tengah, Selat Kalimantan Tengah District has been carried out properly. This is because it is influenced by students' interest, motivation, attention and practice of Religious Education is very high, the high discipline and skills of Religious teachers in teaching as well as the high attention of students, guidance and attitudes of the family environment in children's learning.